Challenges in implementing new nursing qualifications (Regulation 174) in South African public nursing colleges: Principal perspectives - Magdeline N. Poto-Rapudi; Thembekile E. Masango; Masenyani O. Mbombi (Curationis, 2025)
Background: The criticism levelled against the legacy nursing programmes has transformed the health education and training system and the preparation of nursing students to meet society’s needs. The prevailing practice in nursing education (NE) change is orientated towards increasing professionalisation, which necessitates expanding nursing programmes to provide universal health coverage. The South African Nursing Council (SANC) has mandated NE institutions to curriculate and institute the new qualifications in nursing.